2022
DOI: 10.3390/nano12030394
|View full text |Cite
|
Sign up to set email alerts
|

N2O Hydrogenation on Silver Doped Gold Catalysts, a DFT Study

Abstract: In this study, the full reaction mechanism for N2O hydrogenation on silver doped Au(210) surfaces was investigated in order to clarify the experimental observations. Density functional theory (DFT) calculations were used to state the most favorable reaction paths for individual steps involved in the N2O hydrogenation. From the DFT results, the activation energy barriers, rate constants and reaction energies for the individual steps were determined, which made it possible to elucidate the most favorable reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous studies have also identified a comparable N 2 O decomposition mechanism on Cu atoms in Cu-ZSM-5 and Cu-porphyrins . The breaking of the N–O bond after N 2 O’s O-terminal adsorption was considered to be the rate-determining step, followed by N 2 desorption. ,, The residual *O subsequently accepted *H, leading to the formation of *OH and H 2 O …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have also identified a comparable N 2 O decomposition mechanism on Cu atoms in Cu-ZSM-5 and Cu-porphyrins . The breaking of the N–O bond after N 2 O’s O-terminal adsorption was considered to be the rate-determining step, followed by N 2 desorption. ,, The residual *O subsequently accepted *H, leading to the formation of *OH and H 2 O …”
Section: Resultsmentioning
confidence: 94%
“…57,59,60 The residual *O subsequently accepted *H, leading to the formation of *OH and H 2 O. 61 The charge density difference diagram of Cu 1 −NCB illustrated the electron interactions between the adsorbed *OH and Cu−N 4 sites, highlighting electron accumulation (yellow regions) and depletion (blue regions) near the Cu atom (Figure 6b). The charge distribution predominantly occurred around the Cu site, forming an electron-rich region that facilitated the reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…N 2 O is a chemically stable and kinetically inert molecule [16], its deoxygenation reaction remains difficult, as even thermal decomposition is limited by a high kinetic barrier despite being thermodynamically favorable [14, 17, 18]. According to the previous reports, most of the degradation of N 2 O relied on metal catalysts, such as Mn, Fe, Co, Ni, Cu, Bi, Ru, Re [19–32]. However, those metals exist obvious weaknesses more or less, such as the complicated ligand preparation process, the harsh reaction conditions, rare and expensive, or the low selectivity from the abundant metals [33, 34].…”
Section: Introductionmentioning
confidence: 99%